Delineation of dual molecular diagnosis in patients with skeletal deformity - Liu, Lian; Sun, Liying; Chen, Yujun; Wang, Muchuan; Yu, Chenxi; Huang, Yingzhao; Zhao, Sen; Du, Huakang; Chen, Shaoke; Fan, Xin; Tian, Wen; Wu, Zhihong; et al. (Orphanet journal of rare diseases, 2022)
Skeletal deformity is characterized by an abnormal anatomical structure of bone and cartilage. In our previous studies, we have found that a substantial proportion of patients with skeletal deformity could be explained by monogenic disorders. More recently, complex phenotypes caused by more than one genetic defect (i.e., dual molecular diagnosis) have also been reported in skeletal deformities and may complicate the diagnostic odyssey of patients. In this study, we report the molecular and phenotypic characteristics of patients with dual molecular diagnosis and variable skeletal deformities. From 1108 patients who underwent exome sequencing, we identified eight probands with dual molecular diagnosis and variable skeletal deformities. All eight patients had dual diagnosis consisting of two autosomal dominant diseases. A total of 16 variants in 12 genes were identified, 5 of which were of de novo origin. Patients with dual molecular diagnosis presented blended phenotypes of two genetic diseases. Mendelian disorders occurred more than once include Osteogenesis Imperfecta Type I (COL1A1, MIM:166200), Neurofibromatosis, Type I (NF1, MIM:162200) and Marfan Syndrome (FBN1, MIM:154700). This study demonstrated the complicated skeletal phenotypes associated with dual molecular diagnosis. Exome sequencing represents a powerful tool to detect such complex conditions.